Inhibition of voltage-dependent potassium channels mediates cAMP-potentiated insulin secretion in rat pancreatic β cells. Issue 2 (4th March 2017) - Liu, Yunfeng; Zhong, Xiangqin; Ding, Yaqin; Ren, Lele; Bai, Tao; Liu, Mengmeng; Liu, Zhihong; Guo, Yangyan; Guo, Qing; Zhang, Yu; Yang, Jing; Zhang, Yi
ABSTRACT: Insulin secretion is essential for maintenance of glucose homeostasis. An important intracellular signal regulating insulin secretion is cAMP. In this report, we showed that an increase of cAMP induced by adenylyl cyclase (AC) activator forskolin or by cAMP analog db-cAMP not only potentiated insulin secretion but also inhibited Kv channels, and these effects were reversed by AC inhibitor SQ22536. The cAMP-mediated Kv channel inhibition resulted in prolongation of action potential duration, which partly accounts for the elevation of intracellular Ca 2+ induced by activation of cAMP signaling. Taken together, the results suggest that Kv channels are involved in cAMP-potentiated insulin secretion in pancreatic β cells.